ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PRODUK KOPI DAN PELAYANAN DI RUMAH KOPI BILLY CABANG MEGAMAS MANADO - Jimmy Rezky Torey; Oktavianus ., Porajouw; Tommy F. Lolowang (Sam Ratulangi University, 2016)
This research aims to measure the level of consumer satisfaction toward coffee products and services in the House Coffee Billy Branches Megamas Manado. The Data used in this research is the primary data. The primary data obtained using the technique of the interview directly to respondents, in this case the consumer products coffee in the coffee House Billy Branches Megamas Manado, using a list of questions (questionnaire) as the tool in data collection. The method used in the sampling is sampling accindental. Analysis of the data that is used is a qualitative descriptive analysis is analyzed using the measurement scale Likert attitude scale installation design and presented using the list of the table and numbers. The results of this research shows that the measurement of the level of consumer satisfaction in the house of coffee Billy Branches Megamas Manado in terms of coffee products and services achieve total score loading data of 2.090 that shows the number of the index measuring consumer satisfaction of 83.6% and is considered very satisfied. This shows that consumers are very satisfied with the coffee products offered and the services provided by the employees in the House Coffee Billy Branches Megamas Manado and to increase consumer satisfaction in terms of product and services, Coffee House party Billy Branches Megamas Manado must pay attention to the quality of coffee products and quality of service offered. This is very important in order to maintain the customers and get more customers and increase sales